Sustaining Young Canadian Baptists in the Faith: Exploring the Connection between Religious Affect and Parental Religious Attendance - Fawcett, Bruce G. (Journal of research on christian education, 2021)
This paper explores the impact of parental religious practice on sustaining positive religious affect among churchgoing young Canadian Baptists. A total of 299 participants between the ages of 12 and 18 years attending a summer youth programme sponsored by the Canadian Baptists of Atlantic Canada, completed the Francis Scale of Attitude toward Christianity as a measure of positive religious affect, together with measures of frequency of church attendance for themselves, their mother and their father. These data identified fathers’ religious attendance as a statistically significant factor augmenting the effect of mothers’ religious attendance for sustaining young Canadian Baptists in the faith. The implications of this finding are discussed for pastoral practice.